Comparison impact functional analysis psychotherapy (FAP) and schema therapy on emotional experience towards spouse, communication patterns and rumination of couples referring to counseling centers in Isfahan city - Torajizade, Marjan; Mohammadi Jalai Farahani, Mojtaba; Taghvaei, Davood (Applied Family Therapy Journal (AFTJ), 2023)
Aim: The purpose of the present study was to compare functional analysis psychotherapy (FAP) and schema therapy on emotional experience towards spouse, communication patterns and rumination of couples referring to counseling centers in Isfahan city. Method: The research method was semi-experimental and pre-test, post-test, and follow-up with two experimental and control groups. The statistical population includes all couples in the age group of 25 to 45 years old in Isfahan city, who were selected by available sampling method, 30 couples (10 couples in the first test group, 10 couples in the second test group, and 10 couples in the control group) And for the first group, the performance analysis therapy experiment was presented during 12 sessions, and for the second group, the schema therapy experiment was also presented during 8 sessions. Data collection tools included Brashaw's 6-question emotional experience questionnaire (2009), Christensen and Salawi's (1984) 35-question communication patterns questionnaire, Nolen-Hoeksma and Morrow's (2008) 22-question rumination questionnaire. To analyze the data, the statistical method of analysis of variance with repeated measurements was used. Results: The results showed that there is a difference between the effect of the two psychotherapy methods, performance analysis and schema therapy, on the emotional experience towards the spouse (f=0.33 and p=0.71) and couples' communication patterns (f=0.004 and p=0.97) There was no significant difference, but there was a significant difference between the two psychotherapy methods, performance analysis and schema therapy, on rumination (f=4.40 and p=0.03). Conclusion: Therefore, the schema therapy method in the treatment of rumination and reducing marital conflicts has been a more effective method than performance analysis psychotherapy.